BERKACA NU DAN MUHAMMADIYAH DALAM MEWUJUDKAN NILAI-NILAI MODERASI ISLAM DI INDONESIA - Almu?tasim, Amru (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2019)
Maintaining the moderation of Islam in Indonesia is a must because it is a command of the Qur'an. Didin Hafidhuddin said; Moderate does not mean that all religions are equal in line with the Ministry of Religion and MUI. Collaborative Cadre of Moderate Missionaries Muhammadiyah moderate and not excessive